Nilai-Nilai Pedagogi dalam Filsafat Pestalozzi - Enung Hasanah (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2022)
In globalization, education is the main foundation for developing the potential of human resources in every country. In realizing ideal educational outcomes, it is necessary to create positive pedagogical values that allow students to grow optimally according to their essential potential. One of the educational philosophies that influence modern educational practice almost worldwide is Pestalozzi's philosophy of education. The purpose of this study is to explore the pedagogical values in Pestalozzi's philosophy. This research is a literature study, and it analyzes Pestalozzi's pedagogical values to be developed as positive pedagogic values in schools today. The analyzed documents were open access and peer-reviewed papers, or articles related to Pestalozzi from ERIC, Mendeley, Academia Edu, and CiteSeerX. It was found that ten documents met the requirements and contained data of Pestalozzi's pedagogy. The results showed that the main pedagogical values of Pestalozzi were the pedagogical values of love and moral values. Both values remain reliable as the basis for the development of classroom management by current teachers. Further research on compassion and moral-based pedagogy needs to be conducted.